Theoretical and experimental assessments of accuracy of nonorthogonal mems sensor arrays - Sushchenko, Olha; Bezkorovainyi, Yurii; Novytska, Nataliia (Eastern-European Journal of Enterprise Technologies, 2018)
The paper deals with theoretical and practical assessments of nonorthogonal configurations of MEMS sensors based on both the uniaxial gyroscopes and the triaxial inertial measuring units. The main goal of the paper is research of the possibility to use nonorthogonal redundant configurations in navigation applications. Methods of inertial navigation, analytical mechanics, mathematical statistics and simulation were used in the research. Analysis of nonorthogonal redundant configurations of uniaxial MEMS sensor arrays including matrices of directional cosines has been carried out. Description of nonorthogonal redundant MEMS sensor array based on inertial measuring units (MPU-6050) is represented. Tables of directional cosines for nonortogonal redundant MEMS arrays based on inertial measuring units with such constructive elements as triangular and tetragonal pyramids are obtained. The mutual location of measuring axes for these configurations is given. Features of dynamic test including equipment possibilities and technique of random errors determination are described. Using of the three-degree-of-freedom test bench provides the simulation of the developed MEMS sensor arrays in conditions close to the real operation. The theoretical assessment of accuracy of nonorthogonal redundant MEMS sensor arrays based on both the uniaxial gyroscopes and the triaxial inertial measuring units is carried out. The assessment is implemented using correlation matrices of errors. The experimental assessment of the MEMS array based on triaxial inertial measuring units is determined based on the results of the dynamic analysis. The appropriate graphical dependences including graphs of relative variances and histograms of the random errors distribution are presented. Comparative analysis of the obtained assessments is given. The results can be useful for the design of navigation systems, for example, unmanned aerial vehicles or rockets for the launch of satellites into orbit.